CLINICAL STUDY OF INTRA-ABDOMINAL PRESSURE IN PATIENTS WITH ACUTE ABDOMINAL CONDITIONS: A PROSPECTIVE STUDY. - Kumar, Shubham; Sah, Sujit Kumar; Kumari, Rinku; Gupta, Neha; Jaiswal, Pradeep; Jha, Pawan Kumar (Student's Journal of Health Research Africa, 2024)
Background: Objectives: This study explores the connection between elevated pressure within the abdominal cavity and the onset of acute abdomen, aiming to understand its prevalence, its effect on the functioning of organs, and the efficacy of early interventions for improved patient outcomes. Methods: The study, conducted in the Department of General Surgery of Indira Gandhi Institute of Medical Sciences (IGIMS) in Patna, Bihar, India, between January 2022 to December 2023 enrolled 150 participants diagnosed with acute abdomen based on specific criteria. Following WSACS guidelines, intra-abdominal pressure (IAP) measurements categorized patients into normal and elevated IAP groups, further unveiling distinct intra-abdominal hypertension (IAH) subgroups. Utilizing IBM SPSS and Statistica, the statistical analysis explored correlations, group differences, and regression, offering valuable insights into the impact of IAH on patient outcomes. Results: The study consisted of 150 acute abdomen patients, in which those with intra-abdominal hypertension (IAH) (n=90) showed a significant mortality rate of 40%, compared to 22.5% in the normal pressure group (n=60). Stratifying IAH patients by IAP levels revealed distinct mortality rates: 29%, 35%, 50%, and 80% in the four groups respectively. Statistical analyses revealed prominent correlations between mean IAP and key clinical parameters, including an extremely strong positive correlation between APP and FG. The trends depicted a gradual increase in SOFA score and CVP values with rising IAP levels, peaking in the fourth group. Conclusion: The study highlights the significant effect of IAH on organ perfusion and patient outcomes in acute abdomen. These findings underscore the importance of early recognition and targeted interventions to improve prognosis and reduce mortality. Recommendation: The study recommends implementing proactive measures for early detection and management of IAH in the acute abdomen to enhance patient outcomes.